DETECTing Merkel Cell Polyomavirus in Merkel Tumors - Arora, Reety; Gupta, Komal; Vijaykumar, Anjali; Krishna, Sudhir (Frontiers in Molecular Biosciences, 2020)
Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer caused either by Merkel cell polyomavirus (MCV) T antigen expression, post integration (~80% cases), or by UV-mediated DNA damage. Interestingly, overall survival of MCV-positive Merkel cell carcinoma patients is better, making this differential information of significant diagnostic and prognostic value. Also, MCV provides a direct target for therapy in MCC patients. Currently, the methods used for diagnosis of MCV in tumours are often discordant and unreliable. Here we used a guided molecular scissors based - DNA Endonuclease Targeted CRISPR Trans Reporter (DETECTR) technique to develop an in vitro molecular diagnostic tool for MCV-positive MCC. DETECTR couples recombinase polymerase based amplification of target MCV DNA with Cas12a mediated detection. CRISPR diagnostics couple specific detection followed by cutting of the pathogenic DNA by the Cas enzyme – gRNA complex, with non-specific cutting of ssDNA that provides a measurable visual cue. To detect MCV DNA in MCC, we designed Cas12a gRNAs targeting the MCV DNA and tested their targeting efficiency, and sensitivity using a fluorophore quencher labeled reporter assay. We show that MCV DETECTR system can detect MCV integrated in Merkel tumour rapidly, specifically and with femto-molar sensitivity. This new system is promising and we hope it can be coupled with immunohistochemical studies to diagnose the viral status of MCC in clinics soon.